Mapping Antimicrobial Stewardship in Undergraduate Medical, Dental, Pharmacy, Nursing and Veterinary Education in the United Kingdom. - Enrique Castro-Sánchez; Lydia N Drumright; Myriam Gharbi; Susan Farrell; Alison H Holmes (PLoS ONE)
Objectives To investigate the teaching of antimicrobial stewardship (AS) in undergraduate healthcare educational degree programmes in the United Kingdom (UK). Participants and methods Cross-sectional survey of undergraduate programmes in human and veterinary medicine, dentistry, pharmacy and nursing in the UK. The main outcome measures included prevalence of AS teaching; stewardship principles taught; estimated hours apportioned; mode of content delivery and teaching strategies; evaluation methodologies; and frequency of multidisciplinary learning. Results 80% (112/140) of programmes responded adequately. The majority of programmes teach AS principles (88/109, 80.7%). 'Adopting necessary infection prevention and control precautions' was the most frequently taught principle (83/88, 94.3%), followed by 'timely collection of microbiological samples for microscopy, culture and sensitivity' (73/88, 82.9%) and 'minimisation of unnecessary antimicrobial prescribing' (72/88, 81.8%). The 'use of intravenous administration only to patients who are severely ill, or unable to tolerate oral treatment' was reported in ~50% of courses. Only 32/88 (36.3%) programmes included all recommended principles. Discussion Antimicrobial stewardship principles are included in most undergraduate healthcare and veterinary degree programmes in the UK. However, future professionals responsible for using antimicrobials receive disparate education. Education may be boosted by standardisation and strengthening of less frequently discussed principles.